Post-covid syndrome – current challenge in the work of the general practitioner - Pušica, Irena; Lončar, Ana (General Practice, 2024)
Introduction. Post-COVID syndrome is characterizedby a wide range of clinical symptoms that persist for morethan three months after the initial SARS-CoV-2 infection.Objective. Our objective was to confirm and explorethe long-term effects of post-COVID syndrome, the prevalenceof individual symptoms, and the factors that may influencetheir occurrence.Method. In our study, we conducted a cross-sectionalanalysis on patients who had previously been infected withSARS-CoV-2. Participants were requested to complete thequestionnaire during the latter part of 2023. The data was examinedusing descriptive statistics, the Kruskal-Wallis test,and the Bonferroni test for multiple pair comparisons usingSPSS 26. A p-value
Keywords: ARS-CoV-2; COVID-19; post-acute COVID- 19 syndrome